2013
DOI: 10.1002/jgrb.50274
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of P and S wave energy radiated from very small shear‐tensile seismic events in a deep South African mine

Abstract: [1] We discuss requirements for reliable estimates of radiated seismic energy in S and P phases and derive ratios of S-to-P radiated energy (E S /E P ) of 539 seismic events with local magnitudes À 5.23 ≤ M L ≤ À 2.41 (subdecimeter size) recorded by high-frequency acoustic emission (AE) sensors of the JAGUARS seismic network in the Mponeng deep gold mine, South Africa. The analyzed events are aftershocks of a M W 1.9 earthquake, and the recording AE sensors are located within about 40 m of the events. A shear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 50 publications
2
68
0
Order By: Relevance
“…Based on theoretical considerations by Eaton et al (2014), who showed that tensile events have S/P ratios that do not exceed 4.617, we infer that events with large S/P ratios are shear dominated, whereas those with low S/P ratios may have a significant tensile component. Similarly, Kwiatek and Ben-Zion (2013) inferred the possible presence of tensile components using energy ratios of S and P waves. A more detailed analysis of S/P-wave amplitude ratios would require a better understanding of the spatial sensitivity to P and S waves of the piezosensors.…”
Section: Cluster Analysis and Relative Locationmentioning
confidence: 99%
“…Based on theoretical considerations by Eaton et al (2014), who showed that tensile events have S/P ratios that do not exceed 4.617, we infer that events with large S/P ratios are shear dominated, whereas those with low S/P ratios may have a significant tensile component. Similarly, Kwiatek and Ben-Zion (2013) inferred the possible presence of tensile components using energy ratios of S and P waves. A more detailed analysis of S/P-wave amplitude ratios would require a better understanding of the spatial sensitivity to P and S waves of the piezosensors.…”
Section: Cluster Analysis and Relative Locationmentioning
confidence: 99%
“…Overall, the amplitudes of P-waves relative to S-waves are thus expected to be higher for tensile fracture earthquakes than for shear earthquakes, thereby providing a standard method for identifying the former (or for determining the relative contributions of tensile and shear deformations for 'hybrid' events) (e.g. Walter & Brune 1993;Ramsey & Chester 2004;Šílený et al 2009;Song & Toksöz 2011;Vavryčuk 2011;Kwiatek & Ben-Zion 2013;Eaton et al 2014;Song et al 2014). However, even so, the Appendix shows that the S-wave radiated by a tensile fracture earthquake will usually be stronger than the P-wave, especially in rocks with a low Poisson's ratio.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…We assumed the isotropic medium with constant P-wave velocity. For each synthetic fault plane, the expected P-wave amplitudes were calculated using the radiation pattern formula derived in Ou (2008) and Kwiatek and Ben-Zion (2013) at 24 sensors located at equal distances from hypocenters covering the whole focal sphere (Fig. 2).…”
mentioning
confidence: 99%